2020
DOI: 10.1177/0961203320969806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of autoimmune cytopenias on severity of childhood-onset systemic lupus erythematosus: A single-center retrospective cohort study

Abstract: Objective To assess whether children with autoimmune cytopenias prior to or at diagnosis of systemic lupus erythematosus (cSLE), differ phenotypically from other cSLE patients; and have a lower risk and severity of lupus nephritis (LN) as observed in prior adult studies. To assess the effect of prior immune therapy for autoimmune cytopenias on 2-year risk of LN. Methods This was a retrospective cohort study of incident cSLE cases. We included patients aged less than 17 years at diagnosis. We excluded patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…SLE patients with lymphopenia have reduced surface expression of complement regulatory proteins and endogenous production of type 1 interferon [34]. An analysis of autoimmune cytopenia before or at childhood-onset SLE showed that patients with autoimmune cytopenia had a lower incidence of arthritis and a lower 2-year incidence of LN than those without autoimmune cytopenia [35]. Herein, cytopenia is not a typical finding of a particular cluster and might occur through the different etiologies of arthritis and renal involvement in SLE.…”
Section: Discussionmentioning
confidence: 97%
“…SLE patients with lymphopenia have reduced surface expression of complement regulatory proteins and endogenous production of type 1 interferon [34]. An analysis of autoimmune cytopenia before or at childhood-onset SLE showed that patients with autoimmune cytopenia had a lower incidence of arthritis and a lower 2-year incidence of LN than those without autoimmune cytopenia [35]. Herein, cytopenia is not a typical finding of a particular cluster and might occur through the different etiologies of arthritis and renal involvement in SLE.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4] However, little data is available regarding the implications of the use of belimumab in a "real-world" setting for the treatment of childhood-onset SLE (cSLE). 6,7 In this context, we read with great interest a paper by Roberts et al 7 in this journal. For the past 5 years, we have also used belimumab add-on treatment in nine patients with cSLE.…”
Section: Sirmentioning
confidence: 97%
“…Real-world use and outcomes of biologics were recently reported in cSLE. A case series of 21 cSLE patients under belimumab ≥12 months showed that the median dose of prednisone was significantly reduced throughout 1 year (12.5 mg/day at baseline vs. 9 at 6 months vs. 5 at 12 months), however no difference was evidenced in SLEDAI-2K scores [47]. A multivariate analysis of a prospective multicenter Chinese study with 193 active cSLE under belimumab treatment showed that SELENA-SLEDAI score <10 at baseline and low glucocorticoid dose predicted achievement of LLDAS, and a low glucocorticoid dose also predicted achievement of clinical remission [48].…”
Section: General Management and Drug Treatmentmentioning
confidence: 99%